Disruption of the foxe1 gene in zebrafish reveals conserved functions in development of the craniofacial skeleton and the thyroid - Raterman, Sophie T.; Von Den Hoff, Johannes W.; Dijkstra, Sietske; De Vriend, Cheyenne; Te Morsche, Tim; Broekman, Sanne; Zethof, Jan; De Vrieze, Erik; Wagener, Frank A. D. T. G.; Metz, Juriaan R. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Mutations in the FOXE1 gene are implicated in cleft palate and thyroid dysgenesis in humans. Methods: To investigate whether zebrafish could provide meaningful insights into the etiology of developmental defects in humans related to FOXE1, we generated a zebrafish mutant that has a disruption in the nuclear localization signal in the foxe1 gene, thereby restraining nuclear access of the transcription factor. We characterized skeletal development and thyroidogenesis in these mutants, focusing on embryonic and larval stages. Results: Mutant larvae showed aberrant skeletal phenotypes in the ceratohyal cartilage and had reduced whole body levels of Ca, Mg and P, indicating a critical role for foxe1 in early skeletal development. Markers of bone and cartilage (precursor) cells were differentially expressed in mutants in post-migratory cranial neural crest cells in the pharyngeal arch at 1 dpf, at induction of chondrogenesis at 3 dpf and at the start of endochondral bone formation at 6 dpf. Foxe1 protein was detected in differentiated thyroid follicles, suggesting a role for the transcription factor in thyroidogenesis, but thyroid follicle morphology or differentiation were unaffected in mutants. Discussion: Taken together, our findings highlight the conserved role of Foxe1 in skeletal development and thyroidogenesis, and show differential signaling of osteogenic and chondrogenic genes related to foxe1 mutation.